Resposta do milho cultivado em sistema de plantio direto à aplicação de doses de nitrogênio e cultivo de plantas de cobertura em pré-safra - Moda, Leandro Rosatto [UNESP]; Santos, Carlos Leandro Rodrigues dos [UNESP]; Flores, Rilner Alves; Borges, Bernardo Melo Montes Nogueira [UNESP]; Andrioli, Itamar [UNESP]; Prado, Renato De Mello [UNESP] (My University, 2014)
The use of cover crops can produce large amounts of biomass, improving the cycling of nutrients, particularly nitrogen, promoting productivity gains and cost savings. Given this, the objective was to evaluate the use of N rates associated to cover crops grown in pre-harvest nutritional status, nitrogen accumulation and corn yield in both years. The experiment was conducted in an Oxisol with maize, no-tillage system. The experimental design was a randomized block, split plot with four replications. The main treatments were: six cropping systems (sun hemp, jack bean, lablab, millet, and velvet bean fallow) in secondary treatments: four doses of nitrogen (0, 60, 120 and 180 kg ha-1N). Corn yield was not affected by the type of coverage for pre-season, regardless of the nitrogen applied in the soil. Still, the use of nitrogen fertilizer in the soil promotes gains in grain yield in the first year of cultivation, regardless of the type of coverage in pre-season. In the first year (2006/2007) the species of coverage produced more biomass were velvet bean, jack bean, sun hemp and lablab, while in the second year (2007/08) were the sun hemp, millet, lablab, jack bean and velvet bean, respectively.
Response of corn grown in tillage system for the application of nitrogen doses in a sequence of plant cover
Keywords: Fallow plants; Jack bean; Millet; N-mineral; Sun hemp; Velvet bean